Behaviour of ultra high performance fibre reinforced concrete columns subjected to blast loading. (1st July 2016) - Xu, Juechun; Wu, Chengqing; Xiang, Hengbo; Su, Yu; Li, Zhong-Xian; Fang, Qin; Hao, Hong; Liu, Zhongxian; Zhang, Yadong; Li, Jun
Highlights: Blast testing on high strength reinforced columns. Blast testing on ultra high performance fibre reinforced concrete columns. Large axial loading is applied on columns during the blast tests. Abstract: Ultra high performance fibre reinforced concrete (UHPFRC) is a cement-based composite material mixing with reactive powder and steel fibres. It is characterized by its high strength, high ductility and high toughness and such characteristics enable its great potential in protective engineering against extreme loads such as impact or explosion. In the present study, a series of field tests were conducted to investigate the behaviour of UHPFRC columns subjected to blast loading. In total four 0.2 m × 0.2 m × 2.5 m UHPFRC columns were tested under different designed explosions but all at a standoff distance of 1.5 m. Blast tests were also performed on four high strength reinforced concrete (HSRC) columns with the same size and reinforcement as UHPFRC columns to evaluate their behaviour under the same loading conditions. The data collected from each specimen included reflected overpressures, column deflections at centre and near the supports. Three major damage modes, including flexural, shear and concrete spalling failure modes, were observed. The post blast crack patterns, permanent deflections and different levels of damage observations showed that UHPFRC columns performed superior in blast loading resistance as compared with HSRC columns.